2002
DOI: 10.1191/0267659102pf536oa
|View full text |Cite
|
Sign up to set email alerts
|

Should we rely on nasopharyngeal temperature during cardiopulmonary bypass?

Abstract: A potential morbidity of incomplete re-warming following hypothermic cardiopulmonary bypass (CPB) is cardiac arrest. In contrast, attempts to fully re-warm the patient can lead to cerebral hyperthermia. Similarly, rigid adherence to 37.0 degrees C during normothermic CPB may also cause cerebral overheating. The literature demonstrates scant information concerning the actual temperatures measured, the sites of temperature measurement and the detailed thermal strategies employed during CPB. A prospective, random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
(12 reference statements)
1
19
0
2
Order By: Relevance
“…The reason for early impaired cerebral oxygenation during warm CPB in the previous studies (9, 10, 22, 23) was because patients were exposed to the risk of continuous rewarming from the beginning of CPB to keep bypass temperature at >35°C or strictly at 37°C. More importantly, there is an increased risk of undetected brain hyperthermia during rewarming because nasopharyngeal and oesophagyeal temperatures underestimate brain temperature (24–27). Recently, avoidance of early rewarming during warm CPB (35 ± 1°C) in children has been reported to prevent desaturation (28), which has been described at the first 40 min of warm CPB (10).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for early impaired cerebral oxygenation during warm CPB in the previous studies (9, 10, 22, 23) was because patients were exposed to the risk of continuous rewarming from the beginning of CPB to keep bypass temperature at >35°C or strictly at 37°C. More importantly, there is an increased risk of undetected brain hyperthermia during rewarming because nasopharyngeal and oesophagyeal temperatures underestimate brain temperature (24–27). Recently, avoidance of early rewarming during warm CPB (35 ± 1°C) in children has been reported to prevent desaturation (28), which has been described at the first 40 min of warm CPB (10).…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and colleagues [11] (2002) highlighted, in a prospective study of 80 patients, the disparity in temperature measurement between the NP temperature and the arterial outlet temperature. In 2004, Kaukuntla and colleagues [12] demonstrated that commonly used core temperature monitoring sites (bladder, esophageal, and NP) were not accurate measures of cerebral temperature where JB temperature is used as the gold standard.…”
Section: Optimal Site For Temperature Measurementmentioning
confidence: 98%
“…One found that esophageal, nasopharyngeal and pulmonary artery assessments had the closest correlation to cerebral temperature 92 . The second paper found that nasopharyngeal temperatures did not correspond well to arterial temperature measurements 93 .…”
Section: Quality Of Evidence: Moderate Strength Of Recommendation: Stmentioning
confidence: 98%